2015
DOI: 10.1002/ejp.687
|View full text |Cite
|
Sign up to set email alerts
|

Reward responsiveness in patients with chronic pain

Abstract: Background: It is proposed that changes in reward processing in the brain are involved in the pathophysiology of pain based on experimental studies. The first aim of the present study was to investigate if reward drive and/or reward responsiveness was altered in patients with chronic pain (PCP) compared to controls matched for education, age and sex. The second aim was to investigate the relationship between reward processing and nucleus accumbens volume in PCP and controls. Nucleus accumbens is central in rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
1
34
2
Order By: Relevance
“…Recent research has for instance proposed reduced reward responsiveness as a neurobiological marker of chronic pain vulnerability (Denk et al, 2014;Elvemo et al, 2015). With regard to psychosocial risk mechanisms, the Fear-Avoidance Model has proliferated our knowledge on the development and treatment of pain-related disability and distress in adult and pediatric populations (Vlaeyen and Linton, 2000;Leeuw et al, 2007;Asmundson et al, 2012;Goubert and Simons, 2013).…”
Section: Risk Mechanismsmentioning
confidence: 99%
“…Recent research has for instance proposed reduced reward responsiveness as a neurobiological marker of chronic pain vulnerability (Denk et al, 2014;Elvemo et al, 2015). With regard to psychosocial risk mechanisms, the Fear-Avoidance Model has proliferated our knowledge on the development and treatment of pain-related disability and distress in adult and pediatric populations (Vlaeyen and Linton, 2000;Leeuw et al, 2007;Asmundson et al, 2012;Goubert and Simons, 2013).…”
Section: Risk Mechanismsmentioning
confidence: 99%
“…Our review of the literature also indicated that these exemplary factors are highly relevant to chronic pain conditions and may serve as a model for understanding complex associations among pain, smoking, and additional transdiagnostic factors that could be identified in future research. Indeed, chronic pain patients have reported greater levels of anhedonia and decreased responsiveness to rewards, relative to healthy controls (Elvemo, Landrø, Borchgrevink, & Håberg, 2015), and distress tolerance has been implicated in emotion regulation and coping among persons with chronic pain (Hamilton, Karoly, & Kitzman, 2004). Moreover, decades of research have consistently demonstrated that greater levels of anxiety sensitivity predict a range of negative pain-related outcomes, including greater use of analgesic medications, greater cognitive bias toward pain experiences, and greater activation of fear-avoidance mechanisms (e.g., pain-related fear) that contribute to the development and maintenance of pain-related disability (e.g., Asmundson & Norton, 1995; Keogh & Cochrane, 2002; Wong et al, 2014).…”
Section: Anxiety and Depression In Bidirectional Pain–smoking Relationsmentioning
confidence: 99%
“…1417 This phenomena may be explained from a cognitive perspective: a body of evidence suggests that pain (like other aversive experiences and negative emotional states) can narrow and tune attention towards present harms and potential threats. 18 This negative attentional bias, while evolutionarily conserved for its survival value, may result in a kind of “cognitive myopia”, preventing the individual from noticing and appreciating pleasant events and experiences.…”
Section: Introductionmentioning
confidence: 99%